More on a friend of Philippe de Vitry: Johannes Rufi de Cruce alias Jean de Savoie. Issue 1 (9th April 2019) - WATHEY, ANDREW
Abstract: Who was Jean de Savoie, the clerk with whom the composers Jean Campion and Philippe de Vitry penned the jeu-parti Ulixea fulgens in 1350? This article uses Jean's hitherto unnoticed will and foundations at the church of Saint-Benoît-le-Bestourné, Paris, with other documentation, to bring together Jean's two identities in a unified biography (including a new date for his death, in 1354); to illustrate the close parallels between his own career and that of Philippe de Vitry, and to map the scope of opportunities for contact between them in and around the French royal court from the early 1320s onwards. Jean was also an artist and illustrator, and his career as one of the more prominent cartoonists of Philippe VI, king of France, throws light on potential contact with Vitry via the adoption by Louis I de Bourbon of the hitherto largely royal practice of charter illustration. In addition the properties acquired to support two chaplaincies endowed by Jean at Saint-Benoît demonstrate the extent to which he was professionally embedded in a network of royal councillors working in and around the Parlement in the 1330–50s, in which Vitry was also active. Also identified is a house acquired at Saint-Benoît by Gervès du Bus, author of the Roman de Fauvel.